ANALISIS PENGARUH FUNGSI MANAJEMEN PROGRAM KELAS IBU HAMIL TERHADAP CAKUPAN K4 OLEH BIDAN DI PUSKESMAS - Destariyani, Elvi (JURNAL MEDIA KESEHATAN, 2013)
The goal research was analyse influence management pregnant woman class programme to coverage K4 by midwife in Bengkulu city 2012. The kind of this research was kuasi ekspeimen pre test and post tets. The sample were all of midwife (20 persons) that giving implementation for pregnant weman class programme at Penurunan health primary care, Sidomulyo health primary care and Anggut Atas health primary care of Bengkulu City. The result research showed that implementation of management function pregnant weman had not been well in Bengkulu City health primary care. The coverage K4 was still low before material function pregnant woman class programme gave and there was influence management function of pregnant weman programme to coverage K4 before and after gave material function management pregnant weman class in Bengkulu City 2012.